Straw return enhances grain yield and quality of three main crops: evidence from a meta-analysis - Zhang, Ruipeng; Yu, Haiyang; Zhang, Wenbiao; Li, Wei; Su, Hao; Wu, Sixuan; Xu, Qiong; Li, Yaying; Yao, Huaiying (Frontiers in Plant Science, 2024)
Straw return is regarded as a widely used field management strategy for improving soil health, but its comprehensive effect on crop grain yield and quality remains elusive. Herein, a meta-analysis containing 1822 pairs of observations from 78 studies was conducted to quantify the effect of straw return on grain yield and quality of three main crops (maize, rice, and wheat). On average, compared with no straw return, straw return significantly (p < 0.05) increased grain yield (+4.3%), protein content (+2.5%), total amino acids concentration (+1.2%), and grain phosphorus content (+3.6%), respectively. Meanwhile, straw return significantly (p < 0.05) decreased rice chalky grain rate (-14.4%), overall grain hardness (-1.9%), and water absorption of maize and wheat (-0.5%), respectively. Moreover, straw return effects on grain yield and quality traits were infected by cultivated crop types, straw return amounts, straw return methods, and straw return duration. Our findings illustrated that direct straw return increased three main crop grain yields and improved various quality traits among different agricultural production areas. Although improper straw return may increase plant disease risk and affect seed germination, our results suggest that full straw return with covered or plough mode is a more suitable way to enhance grain yield and quality. Our study also highlights that compared with direct straw return, straw burning or composting before application may also be beneficial to farmland productivity and sustainability, but comparative studies in this area are still lacking.